Developing countries' business participation in the AI economy - Douglas Lippoldt (Centre for International Governance Innovation (CIGI), 2025)
How are start-up businesses in middle-income developing countries participating in the rapidly expanding artificial intelligence (AI) economy? Are some developing country AI start-ups able to tap into the AI ecosystems of leading economies in Group of Seven (G7) countries? What is the domestic policy context, and how can conditions be improved? Are there signs of South-South AI ecosystem development? This case study takes stock of the development of AI start-ups engaged with G7 investors and investors from across 10 middle-income developing countries. It considers the emerging investment AI ecosystems in these countries, which are located across Africa, Southeast Asia and Latin America.
Keywords: 330